Modified resin-based nitrogen-containing hard carbon material as well as preparation method and application thereof
By introducing melamine into the phenolic resin to form a triazole heterocyclic covalent polymer resin, and using organic pore makers to adjust the pore structure, the problems of instability and insufficient electrochemical performance of the phenolic resin-based hard carbon material were solved, and high preparation The hard carbon material with nitrogen doping and rich closed-cell structure improves the performance and environmental protection of sodium ion batteries.
Patent Information
- Application Number
- CN202411404524.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The unstable cycle performance and poor rate performance of existing phenolic resin-based hard carbon materials in sodium ion batteries limit their commercial application, and the easy curing properties of the resin materials lead to the formation of cross-linked network structures that are not conducive to excellent electrochemistry. Performance implementation.
By introducing melamine to participate in the polymerization reaction of phenol and formaldehyde, a resin of triazole heterocyclic covalent polymerization is formed, and the pore structure of the material is adjusted simultaneously using organic pore makers to prepare hard with high nitrogen doping and rich closed-pore structures at high temperature carbonization Carbon anode material.
It improves the structural stability and electrochemical performance of the material, enhances the reversible capacity of sodium ion storage, reduces the curing temperature and toxic substance content, improves environmental protection performance, and adjusts the sodium storage performance by regulating the channel structure.
Smart Images

Figure CN119284876A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials and new energy materials, and in particular relates to a modified resin-based nitrogen-containing hard carbon material and a preparation method and application thereof. Background Art
[0002] Among the various LIBs alternative energy storage technologies, sodium-ion batteries (SIBs) have been widely studied due to their low cost, uniform distribution of sodium resources, relatively high energy density, and similar working principles to LIBs. Especially in the fields of large-scale energy storage and slow transportation, it has become a candidate energy storage technology that is expected to partially replace LIBs. For large batteries, cost is very important as a simple evaluation indicator. At the same time, energy and power density are also very important for such devices. Therefore, the key to the development of SIBs is to reduce costs as much as possible while maintaining excellent electrochemical performance. Therefore, it is particularly important to develop novel low-cost and high-performance commercial materials for sodium-ion batteries.
[0003] Among the materials reported so far for SIBs, hard carbon has become one of the most promising anode materials for sodium-ion batteries due to its high performance, sustainability and structural stability. It is worth noting that the precursors of hard carbon that have been studied in depth can be mainly divided into two categories, namely organic polymer materials and biomass materials. Among the many hard carbon precursors, phenolic resin is expected to become a commercial hard carbon precursor due to its advantages such as low cost, mature preparation process and high residual carbon rate. In addition, phenolic resin can control its physical and chemical properties through artificial synthesis, thereby regulating the electrochemical properties of hard carbon materials, which is conducive to the study of hard carbon energy storage mechanism.
[0004] However, although the phenolic resin-based hard carbon anode has reached 410 mAh g -1 The reversible specific capacity of phenolic resin is 2.347 W / m, but its unstable cycle performance and poor rate performance indicate that phenolic resin still cannot be used as a high-quality hard carbon precursor, which is also a common problem of phenolic resin-based hard carbon materials. It is worth mentioning that the resin material has the characteristic of easy curing, and the tightly cross-linked network structure formed is conducive to the formation of hard carbon materials with low specific surface area, high structural stability and rich in nanopores. These three structural characteristics will bring excellent electrochemical performance. Therefore, in order to realize the commercialization of sodium-ion batteries, it is particularly important to find a new resin hard carbon precursor. It is well known that by changing the subdivision categories of phenolic monomers and aldehyde monomers in the synthetic raw materials or introducing other reagents for modification or mixing, phenolic resins with different properties and structures can be prepared, and finally hard carbon negative electrode materials with their own characteristics are obtained to adjust their electrochemical properties. Summary of the invention
[0005] In view of the above technical problems, the purpose of the present invention is to prepare a modified resin-based nitrogen-containing hard carbon negative electrode material. Phenol-melamine-formaldehyde resin is synthesized by introducing melamine into a phenolic resin system to form a tri-nitrogen heterocyclic covalently polymerized resin molecule, and an organic pore-forming agent is used to adjust the pore structure of the material. After high-temperature carbonization, a hard carbon negative electrode material for sodium ion batteries with high nitrogen doping, rich closed-pore structure, and disordered microstructure is prepared.
[0006] The technical solution of the present invention is as follows:
[0007] The first object of the present invention is to protect a method for preparing a modified resin-based nitrogen-containing hard carbon material, by introducing melamine to participate in the polymerization reaction of phenol and formaldehyde to form a tri-nitrogen heterocyclic covalently polymerized resin.
[0008] The invention introduces melamine to participate in the polymerization reaction of phenol and formaldehyde to form a tri-nitrogen heterocyclic covalently polymerized resin molecule with a stable structure; and simultaneously an organic pore-forming agent forms a rich microporous structure in a polymer matrix.
[0009] In some embodiments, the polymerization reaction further includes a catalyst, and the catalyst includes at least one of asparagine, ethylenediamine, dimethylamine, trimethylamine, 1,6-hexanediamine, diethylenetriamine, lysine, glutamic acid, and aspartic acid.
[0010] In some preferred embodiments, the polymerization reaction further includes a pore-forming agent, and the pore-forming agent includes at least one of tetrapropylammonium hydroxide, polyvinyl alcohol, polyethylene glycol, and hexadecyltrimethylammonium bromide.
[0011] In some embodiments, the molar ratio of phenol to catalyst is 10 to 20:1;
[0012] and / or, the molar ratio of phenol to pore-forming agent is 20 to 50:1;
[0013] and / or, the molar ratio of phenol to melamine is 0.5 to 3:1;
[0014] And / or, the molar ratio of phenol to formaldehyde is 0.5 to 2:1.
[0015] In some preferred embodiments, the polymerization reaction conditions include: temperature 60-120° C., time 1-6 h.
[0016] More specifically, the method for preparing the modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0017] (1) After heating and melting phenol, a certain amount of catalyst is added and stirred evenly to obtain a mixed solution A;
[0018] (2) dispersing a certain amount of formaldehyde monomer in an aqueous solution, heating it to 60° C., then sequentially adding a certain amount of melamine and an organic pore-forming agent, and stirring evenly to obtain a mixed solution B;
[0019] (3) adding the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keeping heating and stirring evenly, to obtain a mixed solution C;
[0020] (4) adding the mixed solution C prepared in step (3) into a reaction kettle and performing a polymerization reaction at a certain temperature for a period of time;
[0021] (5) After the reaction in step (4) is completed, the product is dried and crushed, and then subjected to low-temperature pre-carbonization and high-temperature carbonization to obtain the modified resin-based hard carbon.
[0022] In some embodiments, after the polymerization reaction is completed, carbonization is further included; preferably, the carbonization includes low-temperature pre-carbonization and high-temperature carbonization;
[0023] The low temperature pre-carbonization conditions include: temperature 500-1000°C, time 1-4h;
[0024] And / or, high temperature carbonization, the conditions include: temperature 1200-1800°C, time 2-8h.
[0025] In some embodiments, the carbonization atmosphere of the low-temperature pre-carbonization and / or high-temperature carbonization comprises an inert gas.
[0026] Another object of the present invention is to protect the modified resin-based nitrogen-containing hard carbon material prepared by the above preparation method.
[0027] The last object of the present invention is to protect the application of the above-mentioned modified resin-based nitrogen-containing hard carbon material in sodium ion batteries.
[0028] Preferably, it is used as a negative electrode material for sodium ion batteries.
[0029] Compared with the prior art, the advantages of the present invention are:
[0030] 1. Unlike traditional phenolic resins, the introduction of melamine will participate in the co-condensation reaction of phenol and formaldehyde. On the one hand, it will reduce the curing temperature of phenolic resin, accelerate the reaction rate, and shorten the reaction time. On the other hand, it will reduce the content of toxic substances such as free phenol and free aldehyde, and improve the environmental performance of the resin. In addition, after melamine participates in the reaction, a structurally stable trinitrogen heterocycle is introduced into the resin molecular structure, and after carbonization, a nitrogen-doped hard carbon material is formed. The nitrogen element is evenly distributed inside and on the surface of the carbon material, providing abundant active sites, which is conducive to improving the reversible capacity of sodium ion storage.
[0031] 2. Organic pore formers are linear molecular compounds. On the one hand, they have good toughness and elasticity, which is beneficial to improving the strength of carbon materials. On the other hand, they form tiny micelles inside the polymer, which form rich pore structures after carbonization. By adjusting the proportion of pore formers and the carbonization temperature, the closed-pore structure can be finely controlled, thereby adjusting the sodium storage performance of hard carbon materials.
[0032] 3. Different from the traditional NaOH or ammonia catalyst, the present invention uses amines or amino acids as catalysts, which promotes the polymerization reaction and makes the polymerization reaction proceed smoothly and evenly, which is conducive to the formation of uniform pores in the phenolic resin carbon and a more uniform microstructure. In addition, this type of organic catalyst has no ash residue problem during the carbonization process. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a diagram of the polymerization reaction mechanism of the phenol-melamine-formaldehyde resin of the present invention;
[0034] Figure 2 is an electron microscope scanning image of the modified resin-based hard carbon material prepared in Example 1 of the present invention;
[0035] Figure 3 These are the first two charge and discharge curves of the modified resin-based nitrogen-containing hard carbon material of Example 1 of the present invention as the negative electrode of a sodium ion battery at 0.1C. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0037] Example 1
[0038] A method for preparing a modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0039] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.1 mol of asparagine to prepare a mixed solution A.
[0040] (2) Disperse 2 mol of formaldehyde in 20 mol of water, heat to 60° C., then add 0.5 mol of melamine and 0.05 mol of tetrapropylammonium hydroxide in sequence, stir to dissolve, and stir evenly to obtain a mixed solution B.
[0041] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0042] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 90°C for 3 h.
[0043] (5) After drying the sample prepared in step (4), heat it to 600°C at a heating rate of 5°C / min in an argon atmosphere and keep it at that temperature for 2 hours. After grinding the prepared sample, heat it to 600°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1400°C at a heating rate of 2°C / min and keep it at that temperature for 4 hours.
[0044] Example 2
[0045] A method for preparing a modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0046] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.05 mol of ethylenediamine to obtain a mixed solution A.
[0047] (2) Disperse 1 mol of formaldehyde in 20 mol of water, heat to 60° C., then add 1 mol of melamine and 0.02 mol of polyvinyl alcohol in sequence, stir to dissolve, and stir evenly to obtain a mixed solution B.
[0048] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0049] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 60°C for 6 hours.
[0050] (5) After drying the sample prepared in step (4), heat it to 500°C at a heating rate of 5°C / min in an argon atmosphere and keep it warm for 4 hours. After grinding the prepared sample, heat it to 500°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1200°C at a heating rate of 2°C / min and keep it warm for 8 hours.
[0051] Example 3
[0052] A method for preparing a modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0053] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.08 mol of 1,6-hexanediamine to obtain a mixed solution A.
[0054] (2) Disperse 0.5 mol of formaldehyde in 20 mol of water, heat to 60° C., then add 2 mol of melamine and 0.03 mol of hexadecyltrimethylammonium bromide in sequence, stir to dissolve, and stir evenly to obtain a mixed solution B.
[0055] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0056] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 120°C for 1 h.
[0057] (5) After drying the sample prepared in step (4), heat it to 1000°C at a heating rate of 5°C / min in an argon atmosphere and keep it at that temperature for 1 hour. After grinding the prepared sample, heat it to 1000°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1800°C at a heating rate of 2°C / min and keep it at that temperature for 2 hours.
[0058] Example 4
[0059] A method for preparing a modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0060] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.06 mol of glutamic acid to obtain a mixed solution A.
[0061] (2) 1.5 mol of formaldehyde was dispersed in 20 mol of water and heated to 60° C. Then 0.3 mol of melamine and 0.04 mol of polyethylene glycol were added in sequence and stirred to dissolve and mix well to obtain a mixed solution B.
[0062] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0063] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 100° C. for 2 h.
[0064] (5) After drying the sample prepared in step (4), heat it to 800°C at a heating rate of 5°C / min in an argon atmosphere and keep it at that temperature for 2 hours. After grinding the prepared sample, heat it to 800°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1300°C at a heating rate of 2°C / min and keep it at that temperature for 6 hours.
[0065] Comparative Example 1
[0066] A method for preparing a resin-based hard carbon material comprises the following steps:
[0067] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.1 mol of asparagine to prepare a mixed solution A.
[0068] (2) Disperse 2 mol of formaldehyde in 20 mol of water, heat to 60°C, then add 0.05 mol of tetrapropylammonium hydroxide, stir to dissolve, and stir evenly to obtain a mixed solution B.
[0069] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0070] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 120°C for 6 h.
[0071] (5) After drying the sample prepared in step (4), heat it to 600°C at a heating rate of 5°C / min in an argon atmosphere and keep it at that temperature for 2 hours. After grinding the prepared sample, heat it to 600°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1400°C at a heating rate of 2°C / min and keep it at that temperature for 4 hours.
[0072] Comparative Example 2
[0073] A method for preparing a modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0074] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.1 mol of asparagine to prepare a mixed solution A.
[0075] (2) 2 mol of formaldehyde is dispersed in 20 mol of water, heated to 60° C., and then 0.5 mol of melamine is added, stirred to dissolve, and stirred evenly to obtain a mixed solution B.
[0076] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0077] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 90°C for 3 h.
[0078] (5) After drying the sample prepared in step (4), heat it to 600°C at a heating rate of 5°C / min in an argon atmosphere and keep it at that temperature for 2 hours. After grinding the prepared sample, heat it to 600°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1400°C at a heating rate of 2°C / min and keep it at that temperature for 4 hours.
[0079] Comparative Example 3
[0080] A method for preparing a modified resin-based nitrogen-containing hard carbon material comprises the following steps:
[0081] (1) Heat 1 mol of phenol to 60°C to melt it into a liquid state, and stir it evenly with 0.05 mol of NaOH aqueous solution to obtain a mixed solution A.
[0082] (2) Disperse 2 mol of formaldehyde in 20 mol of water, heat to 60° C., then add 0.5 mol of melamine and 0.05 mol of tetrapropylammonium hydroxide in sequence, stir to dissolve, and stir evenly to obtain a mixed solution B.
[0083] (3) Add the mixed solution B prepared in step (2) to the mixed solution A obtained in step (1), keep heating, and stir evenly to obtain a mixed solution C.
[0084] (4) The mixed solution C prepared in step (3) was transferred to a reactor and treated at 120°C for 6 h.
[0085] (5) After drying the sample prepared in step (4), heat it to 600°C at a heating rate of 5°C / min in an argon atmosphere and keep it at that temperature for 2 hours. After grinding the prepared sample, heat it to 600°C at a heating rate of 10°C / min in an argon atmosphere, and then heat it to 1400°C at a heating rate of 2°C / min and keep it at that temperature for 4 hours.
[0086] Table 1: Test results of hard carbon negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-3
[0087]
[0088] The above contents are only basic descriptions of the concept of the present invention, and any equivalent changes made according to the technical solution of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified resin-based nitrogen-containing hard carbon material, characterized in that: By introducing melamine to participate in the polymerization reaction of phenol and formaldehyde, a tri-nitrogen heterocyclic covalently polymerized resin is formed.
2. The preparation method according to claim 1, characterized in that: The polymerization reaction also includes a catalyst, which includes at least one of asparagine, ethylenediamine, dimethylamine, trimethylamine, 1,6-hexanediamine, diethylenetriamine, lysine, glutamic acid, and aspartic acid.
3. The preparation method according to claim 1 or 2, characterized in that: The polymerization reaction also includes a pore-forming agent, which includes at least one of tetrapropylammonium hydroxide, polyvinyl alcohol, polyethylene glycol, and hexadecyltrimethylammonium bromide.
4. The preparation method according to claim 3, characterized in that: The molar ratio of phenol to catalyst is 10 to 20:1; and / or, the molar ratio of phenol to pore-forming agent is 20 to 50:1; and / or, the molar ratio of phenol to melamine is 0.5 to 3:1; And / or, the molar ratio of phenol to formaldehyde is 0.5 to 2:
1.
5. The preparation method according to claim 3 or 4, characterized in that: The polymerization reaction conditions include: temperature 60-120° C., time 1-6 hours.
6. The preparation method according to claim 3 or 4, characterized in that: After the polymerization reaction is completed, carbonization is further included; preferably, the carbonization includes low-temperature pre-carbonization and high-temperature carbonization; The low temperature pre-carbonization conditions include: temperature 500-1000°C, time 1-4h; And / or, high temperature carbonization, the conditions include: temperature 1200-1800°C, time 2-8h.
7. The preparation method according to claim 6, characterized in that: The carbonization atmosphere of the low-temperature pre-carbonization and / or high-temperature carbonization includes an inert gas.
8. A modified resin-based nitrogen-containing hard carbon material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the modified resin-based nitrogen-containing hard carbon material according to claim 8 in sodium ion batteries.
10. The use according to claim 9, characterized in that: Used as negative electrode material for sodium ion batteries.
Citation Information
Patent Citations
Method for quickly synthesizing block graded pore structural nitrogenous porous carbon
CN101723354A
Preparation method for heteratom-containing ordered mesoporous carbon with high specific capacitance
CN102616766A
Preparation method of resin-based spherical activated carbon with controllable pore structure
CN103936004A
Melamine modified resin-based activated carbon as well as preparation method and application thereof
CN117550597A
Spherical hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN117800317A
Cited By
Melamine and phenolic aldehyde composite resin-based hard carbon microspheres as well as preparation method and application thereof
CN121672486A